FACTORS AFFECTING THE INCOME OF FISHERMEN OF SERAYA ISLAND BATAM CITY IN THE SPAWNING SEASON OF DINGKIS (Siganus sp.) - Hafsar, Khairul; Novedri, Muhamad Nazri; Ulfah, Fitria (Politeknik Kelautan dan Perikanan Dumai, 2024)
One of the fish commodities that has great potential to be utilized by the fishermen of Seraya Island is Dingkis (Siganus sp.). During the spawning season, Dingkis experience a high price increase of 5 times the price during the non-spawning season, namely IDR 30,000-60,000/kg. Therefore, Seraya Island fishermen take advantage of this opportunity because Dingkis fish only spawn during a certain season, namely January-February, which coincides with Chinese New Year (Imlek). The aim of the research is to determine the income of Seraya Island fishermen during the Dingkis spawning season and the influence of the price of Dingkis, the number of Dingkis fish caught, and the number of other fish catches on the income of Seraya Island fishermen. The research was conducted on Seraya Island, Batu Legong Village, Bulang District, Batam City in February 2023. Data analysis was used to answer the first objective, namely by calculating income, the second objective was to test the influence of the independent variable on the dependent variable using SPSS type 26 software. The research results show that the average income of Seraya Island fishermen during the Dingkis spawning season is IDR 9,001,143/month. Partial test results on the number of catches of Dingkis fish have an effect on the income of Seraya Island fishermen. The price of Dingkis fish and the number of other fish caught have no influence on the income of Seraya Island fishermen.